The Impact of Embryo Donation Technology on Child Psychological Adjustment and parenting styles: A Comparative Study - Mahya Kaveh; Seyed Hamzeh Hosseini; Hamid Sharif Nia; Sepideh Peyvandi (International Journal of Fertility and Sterility)
Background: Despite remarkable advancements in the use of embryo donation, concerns havearisen regarding its potential effects on the psychological well-being of children conceivedthrough this assisted reproductive technology and their parent-child relationships.  Method: In a cross-sectional analytical study, the psychological adjustment of 31 children aged3 to 7 born through embryo donation was assessed and compared to 30 age-matched childrenfrom families who conceived naturally using the Strengths and Difficulties Questionnaire.Parenting styles within these families were also evaluated using the Baumrind Parenting StylesInventory through clinical interviews.  Results: Although 8 out of 31 children born through embryo donation (25.8%) and 3 out of 30children from natural conception families exhibited psychological maladjustment, this differencewas not statistically significant. Furthermore, parenting styles did not significantly differbetween the two groups.Conclusion: The absence of genetic parent-child relationships does not appear to be a dominantfactor influencing the psychological adjustment of children or parenting styles.